INFORMATION SECURITY INCIDENT MANAGEMENT AT CRITICAL INFRASTRUCTURE FACILITIES - SYSOIENKO, SVITLANA; BABENKO, VIRA; LADA, NATALIIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper analyzes in detail modern approaches, international standards (CobiT, ITIL, ISO/IEC 27000) and national legislation, which regulate cyber incident management, as well as the features of their application in conditions of military conflict. Particular emphasis is placed on the role of state bodies, such as the State Service for Special Communications and Information Protection and CERT-UA, which coordinate cyber protection and incident response measures. The key stages of incident management - preparation, rapid response and recovery - are identified as integral components of the cycle of continuous improvement of the cyber security system. Particular attention is paid to technological tools for increasing the cyber resilience of CI: the implementation of SIEM systems for monitoring and analyzing threats in real time, the automation of response, as well as the use of internationally recognized incident information exchange protocols (for example, Traffic Light Protocol - TLP). The need to form coordinated interdepartmental response teams, clearly allocate roles and areas of responsibility, as well as build effective communication between government agencies, the private sector and CI operators is emphasized. No less important is the emphasis on personnel training: regular trainings, simulation exercises and assessment of the effectiveness of measures using metrics make it possible to maintain a high level of readiness for cyber incidents. The results of the study can become the basis for the development of an integrated national system for managing information security incidents, which will provide an adequate level of strategic facilities protection and contribute to strengthening the state's cyber resilience. The proposed approaches and recommendations have a direct impact on reducing the risks of cyber threats, minimizing potential losses and guaranteeing the continuity of Ukraine's vital functions in the conditions of constant challenges of modern cyberspace.
Keywords: information security; cyber incident; critical infrastructure facility; cyber threat; incident management